Analisis Stabilitas Dinding Penahan Tanah Tipe Kantilever Akibat Beban Gempa pada Lereng Gunung Argopuro, Desa Kemiri, Jember - Kia Candra Kusuma; Arief Alihudien; Ilanka Cahya Dewi (Jurnal Rekayasa Infrastruktur HEXAGON, 2026)
Kemiri Village, Panti Subdistrict, Jember Regency is an area located on the slopes of Mount Argopuro and has a high potential for landslides due to its steep topography and volcanic soil characteristics that are prone to instability. This study aims to analyze the stability of cantilever-type retaining walls as a mitigation measure against potential slope failures, both under static conditions and when subjected to seismic loads. The research method employed is applied research utilizing geotechnical data from field and laboratory tests, including soil unit weight, cohesion, and internal friction angle. The analysis was conducted in accordance with SNI 8460:2017 by examining safety factors against the hazards of overturning, sliding, and soil bearing capacity. The results indicate that a cantilever RWS with a total height of 4.2 m and a foundation width of 3 m provides an adequate level of safety. Under static conditions, the safety factor against overturning was 4.37 and against sliding was 2.30. Meanwhile, under seismic conditions, the safety factor against overturning was 1.47 and against sliding was 1.49. These values remain above the minimum limits required by the applicable standards. Thus, the planned cantilever retaining wall design is deemed suitable for implementation as a slope stability control solution in the Kemiri Village area